Cell Cycle Control of DNA Replication by Phosphorylation and Dephosphorylation of Replication-Initiation Proteins in Budding Yeast - Zhai, Yuanliang; Yung, Philip Y.K.; Liang, Chun (IntechOpen, 2011)
None